A influência do ambiente domiciliar no desenvolvimento motor de crianças prematuras - Rodrigues, Caroline da Silva; Amaral, Mariana Carvalho do (My University, 2022)
Objective: evaluate the home environment's influence in the motor development of premature children. Materials and Methods: descriptive and observational research with cross-sectional design, with 26 premature babies between 3 and 18 months registered at the Caxias do Sul's Hospital Geral, with premature birth and low birth weight history. To the home environment was utilised the "Affordances in the Home Environment for the Motor Development - Infant Scale" (AHEMD-IS) and to the motor development "Alberta Motor Infant Scale" (AIMS). In statistical analytics was utilised the Shapiro Wilk test and the Spearman Correlation test. Results: It was observed the majority of evaluated babies have shown motor development within normality, in the stimulation variety the majority of children had excellent results and there is a weak, inverse and no significant correlation between the number of children who lived in the home environment and the motor development. Nonetheless, the residence's physical space obtained a moderate and significant correlation with the motor development. Conclusion: The research's results have shown the appropriate physical space had a moderate and significant correlation with the evaluated children's motor development. [resumo fornecido pelos autores]
Objetivo: Avaliar a influência do ambiente domiciliar no desenvolvimento motor de crianças prematuras. Materiais e métodos: Pesquisa descritiva e observacional, com delineamento transversal, com 26 bebês prematuros de 3 a 18 meses cadastrados no Hospital Geral de Caxias do Sul, com nascimento prematuro e baixo peso. Para o ambiente domiciliar foi utilizada a Affordances in the Home Environment for Motor Development ? Infant Scale (AHEMD-IS) e para o desenvolvimento motor a Alberta Motor Infant Scale (AIMS). Na análise estatística foi utilizado o teste Shapiro Wilk e o teste de correlação de Spearman. Resultados: Observou-se que a maioria das crianças avaliadas apresentaram o desempenho motor dentro da normalidade, já na variedade de estimulação a maioria das crianças foi excelente e que há uma correlação fraca e inversa e não significativa entre o número de crianças que vivem no domicílio e o desempenho motor. No entanto, o espaço físico da residência obteve uma correlação moderada e significativa com o desempenho motor. Conclusão: Os resultados do estudo mostraram que o espaço físico apropriado teve correlação moderada e significativa com desempenho motor das crianças avaliadas. [resumo fornecido pelos autores]
Keywords: Prematuros; Crianças - Desenvolvimento; Recém-nascido prematuro - Fatores de risco